2021
DOI: 10.24018/ejmed.2021.3.1.676
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Clinical Characteristics and Lifestyle Habits with Poor Glycemic Control in Patients with Type 2 Diabetes Mellitus

Abstract: Background: The goal of this paper is to explore clinical characteristics and lifestyle habits in patients with type 2 diabetes mellitus and their association with poor glycemic control. Material and Methods: Total of 541 subjects of over 40 years of age with type 2 diabetes mellitus of both genders were included in the study. Anthropometric measurement, glucose level in plasma, HbA1c, triglycerides, AST, ALT, creatinine and eGFR were collected at the time of study entry and patients were asked to fill o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Moreover, in agreement with one study this study found that alcohol consumption was significantly associated with poor GC [ 33 ]. However, other studies [ 34 , 35 ] report alcohol consumption improves GC.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in agreement with one study this study found that alcohol consumption was significantly associated with poor GC [ 33 ]. However, other studies [ 34 , 35 ] report alcohol consumption improves GC.…”
Section: Discussionsupporting
confidence: 92%
“…People with T2D are at elevated risk for suffering different types of cancer, cardiovascular comorbidities, and intravascular complications including nephropathy, retinopathy, and neuropathy, due to hyperglycemia, which sometimes results in insulin resistance (metabolic) syndrome [2]. A variety of lifestyle variables have been linked to the growth of T2D such as a sedentary lifestyle, physical inactivity, food habit, stress, and excessive alcohol use [3]. Globally, diabetes mellitus impacted 285 million adult people in 2021 and is expected to affect 683 million by 2030 [4].…”
Section: Introductionmentioning
confidence: 99%